Adsorption Equilibrium of a Herbicide (Pendimethalin) onto Natural Clay - M.S. El-Geundi; T.E. Farrag; H.M. Abd El-Ghany (Adsorption Science & Technology)
The equilibrium adsorption of a herbicide (pendimethalin) onto natural clay from aqueous solutions was studied experimentally using different system variables. The influence of such variables, such as particle size (d p ), pH and temperature, on the adsorption capacity was studied. Equilibrium modelling was carried out using the Langmuir, Freundlich and Redlich—Peterson models with the corresponding constants being calculated for the different system variables. The results indicate that the maximum adsorption capacity (q max ) at an acidic pH value (3.44) was approximately double that observed at an alkaline pH value (9.62). It was also found that the effect of particle size was significant and that the temperature plays an interesting role in the adsorption process. The enthalpy change (ΔH) for adsorption was evaluated as −29.36 kJ/mol. It is clear from the results of this study that the Freundlich model fitted the experimental adsorption data significantly better than the Langmuir or the Redlich—Peterson models.